Anthropocene and geomorphological changes: Fluvial systems in the centenary Urbanization process of são paulo - Rodrigues, Cleide; Moroz-Caccia Gouveia, Isabel Cristina [UNESP]; Da Luz, Rodolfo Alves; Veneziani, Yuri; Simas, Iury Tadashi Hirota; De Paula Silva, Juliana (Instituto Geologico, 2019)
This paper presents the results of studies in which the Anthropogeomorphological approach, i.e. the Anthropocene Geomorphology, was adopted, tested, and developed, aiming to identify and measure geomorphological changes that occurred in the centenary urbanization process of the metropolitan region of São Paulo. Intervals in history of about a century or less were especially considered, as well as fluvial and fluvial-lacustrine systems, and geoindicators. The results were obtained for different case studies, in different areas and at different spatio-temporal scales. Based on the methodology used, it was possible to identify changes in origin, which can be anthropic, non- anthropic, or complex, and to measure their magnitude. Most of the observed changes - morphological, sedimentary, or erosional - and their rates and balances were considered to be significant for ten-year or hundred-year intervals. These changes tend to occur in thousands or hundreds of thousands of years in natural systems. The high magnitude and velocity of the geomorphological changes indicate that different branches of Earth Science should be considered in current discussions about the Anthropocene, as well as in decision-making regarding environmental planning, and in determining the parameters to increase the resilience of physical systems of the Earth's surface.
Antropoceno E mudanças geomorfológicas: Sistemas fluviais No processo centenário de urbanização De São Paulo
Keywords: Anthropocene; Anthropogeomrophology; Urban Fluvial Systems